GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE IN THE IMPACT OF FINANCIAL PERFORMANCE ON COMPANY VALUES - Dhian Andanarini Minar Savitri; Yuyun Ristianawati; Prihasantyo Siswo Nugroho; Astohar Astohar (International Journal of Economy, Education and Entrepreneurship, 2021)
In the sector of the manufacturing industry that has gone public, the value of the company is very important to attract investors. One thing that is thought to affect the value of the company is financial performance. This study aims to determine the effect of financial performance on firm value with Good Corporate Governance as a moderating variable. In this study, financial performance is proxied by Return on Assets (ROA), firm value is proxied by Price to Book Value (PBV) and Good Corporate Governance is proxied using managerial ownership. The data in this study uses secondary data taken from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2019. The results of this study indicate that financial performance has an effect on firm value, but Good Corporate Governance cannot moderate the effect of financial performance on firm value